CONSUMO DE DROGAS EN EL ADOLESCENTE EN LA CALLE - Sandí Esquivel, Luis (1999)
The goal of this study was to evaluate the functioning of street drug dependent adolescents, 100 subjects in this condition were evaluated and compared with high school students. It was found that the mayority used multiple drugs, crack was the drug of most used. A high percentage of them were seriously affected in all the main domains of their functioning. It is discussed the importance of early detection and intervention.